Effects of different roasting conditions on sugars profile, volatile compounds, carotenoids and antioxidant activities of orange-fleshed sweet potato - Sinian He; Shengsheng He; Liya Niu; Chao Sun; Zicong Zeng; Jianhui Xiao (Food Chemistry: X)
The effects of different roasting conditions (180 °C/70 min (T180), 210 °C/50 min (T210), and 240 °C/30 min (T240) on the qualities of orange-fleshed sweet potato (OFSP) were explored. Changes in sugars and carotenoids were analyzed by GC–MS and LC-MS/MS, and volatile compounds were characterized by GC × GC/TOF-MS. The antioxidant activities (DPPH• and ABTS•+) and bioaccessibility of β-carotene after in vitro digestion were also evaluated. Results showed that sugar content increased with roasting temperature, with T240 showing the highest sugar content (817.53 mg/g). The greatest variety of sugar species was identified in T180, with maltose (53.51 %) and sucrose (25.70 %) being the predominant sugars. In addition, T210 produced the largest number of volatile compounds, with vanillin being key flavor compound. Regarding the antioxidant activities and bioaccessibility in vitro simulated digestion, their capacity was T180 > T210 > T240. In comparison, T210 appears to be the optimal roasting condition, offering a balanced sweetness profile, enhanced flavor complexity, and optimal retention of carotenoids.